The Role of Higher Education Institutions in Developing Sustainable Business : A Phenomenological Approach of College Students’ Start-up - Iwan Sukoco,; Nur Fitri Rahmawati,; Bambang Hermanto,; Arianis Chan, (Technium Social Sciences Journal, 2020)
This study aims at answering questions about what are the obstacles faced by students when running sustainable business and how universities should educate students so that they are not only able to build a business but also understand and be able to develop sustainable business in the start-ups they build. In this study, the phenomenological approach of the qualitative research design was employed. Data collection was carried out by semi-structured interviews to dig deeper into the experiences of informants consisting of 30 start-up student entrepreneurs. Interviews were also conducted with representatives of universities to obtain data related to the efforts of higher education institutions in educating students to be able to build sustainable business. This research shows that 5 variables namely Social and cultural attitude towards youth entrepreneurship, Entrepreneurship education, Access to finance/start-up financing, Administrative and regulatory framework, and Business assistance and supports are barrier factors faced by start up entrepreneurs which need to be improved by universities in order that students can run sustainable business professionally.